Penyusunan Seleksi Penerimaan Pegawai Kontrak Pada PDAM Kota Bengkulu - Angga Gustian Pratama; Indra Kanedi; Achmad Fikri Sallaby (UNIVED Press, 2024)
Computer-based information systems are experiencing significant changes in almost all fields. This is due to the role of computer technology which provides many conveniences and benefits in all fields. Excellence in the field of technology, especially computers, can be an added value for companies that want to win competition in the business world which is so tight, such as using it in assessing someone's personality. The system designed in this research is a new system, the process is that the data obtained from interviews and observations from the preparation of contract employee recruitment selection at PDAM Bengkulu City are entered into the designed system, then input data so that the system will be processed using scoring system method by using application uses a website with PHP MySQL database. From the results of research about identifying interests in PDAM companies based on MBTI personality, several things can be concluded as follows: The research web application is able to help admins recognize and understand applicants' personality interests by providing recommendations for positions that are suitable and in accordance with their MBTI personality type. The research web application is able to have a positive influence on the effectiveness and efficiency of the position major that suits the applicant.